1989
DOI: 10.1149/1.2097050
|View full text |Cite
|
Sign up to set email alerts
|

Sodium /  V 6 O 13 Polymer Electrolyte Cells

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The reports about V 6 O 13 for emerging energy storage are rare. In 1989, Munshi reported the electrochemical performance of V 6 O 13 as cathode materials for sodium polymer electrolyte cells. Afterward, only few related studies were reported .…”
Section: Vanadium Oxidesmentioning
confidence: 99%
“…The reports about V 6 O 13 for emerging energy storage are rare. In 1989, Munshi reported the electrochemical performance of V 6 O 13 as cathode materials for sodium polymer electrolyte cells. Afterward, only few related studies were reported .…”
Section: Vanadium Oxidesmentioning
confidence: 99%
“…electrophilic aromatic substitutions (Mouhtady et al, 2003) or cationic polymerizations (Sage et al, 2004). The highest activity is presently displayed in the context of high-energy batteries, particularly lithium-ion batteries, where alkali, zinc or magnesium trifluoromethyl sulfonates are contained in some of the complex (gel) polymer electrolytes (McLin & Angell, 1992;Munshi et al, 1989;Greenbaum, 1987;Semkow & Sammels, 1987;Forsyth et al, 1997;Zheng et al, 1998;Rhodes et al, 1999Rhodes et al, , 2002Ikeda, Mori, Furuhashi, Masuda & Yamamoto, 1999;Kumar & Munichandraiah, 2000a,b;Mitra et al, 2001;Kumar & Sampath, 2003). Our interest in trifluoromethyl sulfonates originates from the various degrees of rotational freedom available to the anion in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Amita Chandra et al [14] studied a composite polymer electrolyte (PEO+NH4I+AI203) which should improve the film stability. Many rechargeable batteries have also been reported based on the Na § ion conducting polymers [15,16]. In the present paper, we report a new polymer electrolyte PEO+NaCIO3 system.…”
Section: Introductionmentioning
confidence: 79%